The Effect of Thermocycling on Fracture Resistance of CAD- CAM and 3D Printing Provisional Prosthesis - Maab Qassim Hadi; Suha Fadhil Dulami (Journal of Techniques)
This study aims to assess how thermal cycling affected the fracture strength of temporary restorations made using additive 3D printing procedures and computer-aided design- computer-assisted manufacturing (CAD/CAM), subtractive (milling) methods.